Adverse reactions to COVID‐19 vaccines: A practical approach. Issue 6 (14th April 2021) - Rutkowski, Krzysztof; Mirakian, Rita; Till, Stephen; Rutkowski, Ryszard; Wagner, Annette
Abstract: COVID‐19‐related mortality in high‐risk individuals is substantial and current treatment options are limited. There is convincing evidence that the COVID‐19 vaccines reduce the severity of infection and prevent deaths. Three COVID‐19 vaccines are approved in the United Kingdom with many more in development. There are limited data on the triggers and mechanisms of anaphylaxis to these vaccines. We review the potential allergenic compounds in the COVID‐19 vaccines and describe an innovative allergy support model for the vaccination hubs that allows most patients with severe allergy be immunized. Finally, we propose a practical algorithm for the investigations of anaphylaxis to these vaccines.